Effect of an early perinatal depression intervention on long-term child development outcomes: follow-up of the Thinking Healthy Programme randomised controlled trial. (July 2015) - Maselko, Joanna; Sikander, Siham; Bhalotra, Sonia; Bangash, Omer; Ganga, Nima; Mukherjee, Satadru; Egger, Helen; Franz, Lauren; Bibi, Amina; Liaqat, Rakhshanda; Kanwal, Misbah; Abbasi, Tayyaba; et al.
Summary Background Perinatal depression has been linked with deleterious child development outcomes, yet maternal depression interventions have not been shown to have lasting effects on child development, and evidence is not available from countries of low or middle income. In the Thinking Healthy Programme cluster-randomised controlled trial, a perinatal depression intervention was assessed in Pakistan in 2006–07. The intervention significantly reduced depression levels 12 months post partum compared with a control. We aimed to assess the effect of this same intervention on the cognitive, socioemotional, and physical development of children at around age 7 years. Methods Mother–child dyads who participated in the Thinking Healthy Programme cluster-randomised controlled trial were interviewed when the index child was about 7 years old. A reference group of 300 mothers who did not have prenatal depression and, therefore, did not receive the original intervention, was enrolled with their children at the same time. The primary cognitive outcome was the score on the Wechsler Preschool and Primary Scale of Intelligence (WPPSI-IV); primary socioemotional outcomes included scores on the Strengths and Difficulties Questionnaire (SDQ) and the Spence Children's Anxiety Scale (SCAS); and primary physical outcomes were height-for-age, weight-for-age, and body-mass index (BMI)-for-age Z scores. Generalised linear modelling with random effects to account for clustering was the main method of analysis. Analyses were by intention to treat. The Thinking Healthy Programme cluster-randomised trial was registered at ISRCTN.com, number ISRCTN65316374. Findings Of 705 participating mother–child dyads interviewed at the end of the Thinking Healthy Programme randomised controlled trial, 584 (83%) dyads were enrolled. 289 mothers had received the intervention and 295 had received a control consisting of enhanced usual care. The mean age of the children was 7·6 years (SD 0·1). Overall, cognitive, socioemotional, or physical development outcomes did not differ between children in the intervention or control groups whose mothers had prenatal depression. When compared with the reference group of children whose mothers did not have prenatal depression, the Thinking Healthy Programme trial children had worse socioemotional outcomes; mean scores were significantly higher on the SDQ for total difficulty (11·34 vs 10·35; mean difference 0·78, 95% CI 0·09–1·47; p=0·03) and on the SCAS for anxiety (21·33 vs 17·57; mean difference 2·93, 1·15–4·71; p=0·0013). Cognitive and physical outcomes did not differ. Interpretation Our findings show that cognitive, socioemotional, and physical developmental outcomes of children at age 7 years whose mother had prenatal depression did not differ between those who received the Thinking Healthy Programme intervention and those who received the control. Further investigation is needed to understand what types of complex interventions or approaches are needed for long-term gains in maternal and child wellbeing. Prolonged, detailed, and frequent follow-up is warranted for all interventions. Funding Grand Challenges Canada (Government of Canada), Saving Brains programme.